2017
DOI: 10.1007/s00429-017-1366-6
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral lesions of the dorsocentral striatum (DCS) disrupt spatial and temporal characteristics of food protection behavior

Abstract: Spatial and temporal information processing provide a foundation for higher cognitive functions. The survival of animals depends on integrating spatial and temporal information to organize behavior. In general, previous research has focused on only one source of information processing; however, there is evidence to support a convergence in the processing of egocentric-spatial and temporal information within a cortico-striatal system of structures. The current study evaluated the contributions of the dorsocentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Furthermore, the striatum has been reported to be involved in spatial memory; for example, it has been shown that lesions in the dorsal part of the striatum leads to deficits in spatial learning (Block et al, 1993;McDonald and White, 1994;Lee et al, 2014). A recent study in rats also confirmed that a unilateral lesion of this structure can lead to a disruption of spatio-temporal integration (Blankenship et al, 2017), which may lead to think that the dorsal striatum might be involved in our present task.…”
Section: Neuronal Representation Of the Associationmentioning
confidence: 56%
“…Furthermore, the striatum has been reported to be involved in spatial memory; for example, it has been shown that lesions in the dorsal part of the striatum leads to deficits in spatial learning (Block et al, 1993;McDonald and White, 1994;Lee et al, 2014). A recent study in rats also confirmed that a unilateral lesion of this structure can lead to a disruption of spatio-temporal integration (Blankenship et al, 2017), which may lead to think that the dorsal striatum might be involved in our present task.…”
Section: Neuronal Representation Of the Associationmentioning
confidence: 56%
“…Rodent medial frontal cortex, which can be considered analogous to primate prefrontal cortex, is essential for interval-timing behavior as demonstrated by convergent techniques (Kim et al, 2009;Narayanan et al, , 2012Parker et al, 2013aParker et al, , 2014aRossi et al, 2012a). Basal ganglia systems, and particularly the dorsal striatum, are critically involved in interval-timing behavior (Blankenship et al, 2017;Drew et al, 2007;Matell and Meck, 2004;Ward et al, 2009). An important aspect of much of this work is that dopaminergic processing is a key aspect of timing in both the medial frontal cortex and striatum (Drew et al, 2007;Matell and Meck, 2004;Narayanan et al, 2012;Parker et al, 2013aParker et al, , 2014aWard et al, 2009).…”
Section: Studying Cognitive Processing With Interval Timingmentioning
confidence: 99%
“…Rodent medial frontal cortex and dorsomedial striatum are key brain structures for time-based decision making (Blankenship et al, 2017;Coull et al, 2011;Drew et al, 2007;Kim et al, 2009;Matell and Meck, 2004;Meck, 2006;Narayanan et al, , 2012Parker et al, 2013aParker et al, , 2014aRossi et al, 2012a;Ward et al, 2009). Single neurons throughout the frontal cortex and the striatum are prominently modulated across temporal delays (Donnelly et al, 2015;Kimchi and Laubach, 2009;Ma et al, 2014;Narayanan and Laubach, 2009a).…”
Section: Chapter 2: Frontostriatal Activity During Interval Timing Inmentioning
confidence: 99%
See 1 more Smart Citation